Rechterlijk Dwaling dalam Tinjauan Fikih Jinayah dan Hukum Positif - Afidah Wahyuni (Universitas Islam Negeri Jakarta, 2015)
This study shows that jinayah Islamic jurisprudence and criminal law determine how to overcome rechterlijk dwaling by conducting a review of the decision. There are same principals why both rechterlijk dwaling and jinayah Islamic jurisprudence exist. This comes weather from internal and external of the judge. Similarly, the effect and the legal consequences of rechterlijk dwaling, according to both criminal law and jinayah Islamic Jurisprudence.DOI: 10.15408/ajis.v15i2.2860